RETRACTED: Negative transformation of agricultural lands and their protection in JSC "Agricultural enterprise Kolos" of the Kochubeyevsky Municipal District of the Stavropol Territory - Loshakov Alexander; Odintsov Stanislav; Melnik Marina; Kipa Lyudmila; Ivannikov Dmitry (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001